Parametric estimation analysis of compressive stress effects on piezoelectric properties of PZT ceramic - Jong-Ho Kim; Il-Gok Hong; Ho-Yong Shin; Hyo-Jun Ahn; Jong-In Im (Journal of Asian Ceramic Societies, 2024)
ABSTRACTIn this study, the frequency and capacitance of piezoelectric materials due to compressive stress were analyzed, and the overall material properties (compliance matrix, piezoelectric charge constant and dielectric constant) of piezoelectric ceramics were optimized using parametric estimation methods. The piezoelectric ceramic used for optimization was KICET-PZT8, and the compressive stress was applied from a stress-free condition up to 50 MPa. As a result, with increasing compressive stress, the values of [Formula: see text], [Formula: see text] and [Formula: see text] tended to increase, while [Formula: see text]and [Formula: see text] increased and then decreased at 20 MPa or higher. [Formula: see text] and [Formula: see text] showed the maximum values at 40 MPa of compressive stress, with the values reaching 147 pC/N and 375 pC/N, respectively. These values were analyzed to have increased by 117% and 115%, respectively, compared to the stress-free condition. Additionally, the dielectric constant ([Formula: see text]) was found to increase linearly with the applied compressive stress. The understanding of the changes in piezoelectric properties under various compressive stresses derived from this study is expected to be applicable in various ways for the design and application of piezoelectric devices using compressive stresses, including BLT.